Complications of Extended Pelvic Lymph Node Dissection in Patients Undergoing Minimally Invasive Radical Prostatectomy: Analysis and Risk Factors. (22nd October 2022) - Castro, Pedro; Arantes, Paulo B. O.; Martins, Yves M. R.; Reis, Matheus N. M.; Drummond-Lage, Ana Paula; Wainstein, Alberto J. A.
Abstract : Background . The knowledge of risk factors and complications related to extended pelvic lymph node dissection (ePLND) during radical prostatectomy can help selecting patients who will benefit the most with lymph node dissection concomitant to radical prostatectomy. Materials and Methods . Retrospective cohort evaluating 135 patients with PC, with a high risk for lymph node metastasis, submitted to ePLND by a single surgeon between 2013 and 2019, performed either by the laparoscopic or laparoscopic robot-assisted approach. Data related to complications were properly recorded using the Martin's criteria and were classified by the Satava and Clavien–Dindo–Strasberg methods. Logistic regression was used to determine predictors of complications related to ePLND. Results . The mean number of lymph nodes removed was 10.2 ± 4.9, and in 28.2%, they were positive for metastasis. There were five intraoperative complications (4%), all in patients operated by laparoscopic approach. There were nine severe postoperative complications (7.3%), four of which occurred after postoperative day 30. Three patients (2.4%) had thromboembolic complications and five patients (4.0%) had lymphocele that required treatment. There was a correlation between the American Society of Anesthesiologists (ASA) physical status classification and postoperative complications (p = 0.06 ), but it was not possible to identify statistically significant predictors. Conclusion . ePLND during radical prostatectomy has a low rate of intraoperative complications and may change prostate cancer staging. Postoperative complications, especially venous thromboembolism and lymphocele, need to be monitored even in the late postoperative period.